Effect of Storage Conditions on Free Radical Scavenging Activities of Crude Plant Material of Piper longum - Hemalata M. Puntambekar1; Anagha C. Desai2, Pratibha Srivastava1*, Hema N. Raut1 (Journal of Phytology, 2011)
Crude plant material of Piper longum was used for stability studies and kept in stability chambers. The effect of the stored samples on free radical scavenging activity was examined by DPPH, ABTS radical scavenging assays and Deoxyribose degradation assay. Various parameters used for the stability studies were 400C and 75% relative humidity in case of accelerated studies and 30Ã‚Â°C and 65% relative humidity in case of long term studies as per ICH guidelines. Real time studies samples were stored at ambient temperature. Samples were taken out at periodic intervals and suspended in Tris-HCl buffer (10Mm, pH 6.5) to check the total phenolic content and free radical scavenging activity. Outcome of the antioxidant assays indicated that the samples of long term studies showed better antioxidant activity and higher total phenolic content than the samples of accelerated and real time studies.